Content: Evolution & Development 4/2016. Issue 4 (July 2016) - Unknown
Abstract : Cover image: Late fetus of the aardvark, Orycteropus afer, from the collections of the University of Pretoria, Department of Zoology and Entomology, courtesy of Robert Asher (Cambridge), Nigel Bennett and Hermien Viljoen (Pretoria). See Werneburg et al. in this issue.